Does intraspecific variation in Trissolcus japonicus affect its response to non-target hosts? - Nina Häner; Fleur Fenijn; Tim Haye (BioControl, 2024)
Host specificity is a key criterion for the implementation of any biological control program. In parasitoid wasps, host specificity is mediated by their response to chemical cues directly and indirectly associated with their hosts during foraging. Although intraspecific variation in foraging behaviour is documented, it is rarely integrated into risk assessment studies of potential biological control agents, as is the case for Trissolcus japonicus (Ashmead) (Hymenoptera: Scelionidae), an Asian egg parasitoid and biological control agent of the invasive Halyomorpha halys (Stål) (Hemiptera: Pentatomidae). In the present study, we compared the behavioural response of T. japonicus females of an adventive line present in Switzerland and an Asian line (Beijing USDA), recently mass released in Italy, to cues of its target host H. halys and non-target host Pentatoma rufipes (L.) (Hemiptera: Pentatomidae). We observed minimal differences in host acceptance, exploitation and suitability in no-choice tests. In contrast, the behavioural response to host contact kairomones left on leaf substrates significantly differed between the two lines. While both lines preferred chemical footprints of H. halys in comparison to P. rufipes , females of the Beijing USDA line responded more strongly to host kairomones. The observed intraspecific variation in behavioural traits highlights the relevance of considering genetically distinct parasitoid lines and their host foraging behaviour in biological risk assessment studies. However, the implications of intraspecific variation in parasitoid foraging behaviour for biological control of a pest and non-target effects in the field remain challenging to predict.